SYNCHRONIZATION OF ESTRUS IN EWES - I., Fathalla,‎ (The Iraqi Journal of Veterinary Medicine, 1987)
A group of 15 Awasi ewes were inserted with intravaginal sponges of Veramix plus which were removed thirteen days later. Immediately after removal of the sponges, they were injected with 500 IU of FSH intramuscularly. All ewes were came to estrus within 2-3 days after injection. They were serviced, then, after completing a successful pregnancy, all ewes had twin lambs. : This trial indicates the success of estrus synchronization in ewes.